Effect of dislocation density evolution on the thermomechanical response of metals with different crystal structures at low and high strain rates and temperatures (Archives of Mechanics - Test, 2005)
The contribution of plastic strain evolution of mobile and forest dislocation densities to the thermal and athermal components of polycrystalline metals flow stress is investigated in this work. The thermomechanical response is characterized here for body centered cubic (bcc), face centered cubic (fcc) and hexagonal close-packed (hcp) structures of metals at low and high strain rates and temperatures. Consequently, the simulation of the plastic flow stress for these metals is developed based on the concept of thermal activation energy, the additive decomposition of the flow stress, dislocations interaction mechanisms and the role of dislocations dynamic in crystals. The material parameters of the proposed modeling are physically defined and related to the nano- and micro-structure quantities. On the other hand, the hardening parameters of each kind of metal structures are presented in two different forms; physically based definition which is developed, based on the aforementioned concepts and empirical relation which is used by several authors and is based on experimental observations. Several experimental data obtained by different authors for Niobium, Tantalum, Vanadium, Oxygen Free High Conductivity (OFHC) Copper, and Titanium are used in evaluating the proposed models. Good correlation is observed between the proposed models predictions and the experimental observations. Moreover, the predicted results show that the effect of mobile and forest dislocation densities evolution with plastic strain on the thermal stress of bcc metals is almost negligible and pertained totally to the athermal stress part, whereas the plastic strain evolution of these dislocation densities play crucial roles in determining the plastic thermal flow stress of most fcc metals. The thermal and athermal flow stresses for hcp metals, however, show a behavior that is a combination of that for both bcc and fcc plastic deformation models.